Optimizing field work practices in vocational schools by developing a management information system - Mutia Liana; M Lutfi Firdaus; Manap Somantri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The management information system is not yet optimal. This research aims to develop a work practice management information system for vocational school students. The method used in development is the SLDC waterfall model. Management, database, and website feasibility data are obtained through feasibility sheets. Trial data via questionnaire. Descriptive data analysis. The results of the feasibility assessment of the work practice management information system carried out by management experts, database experts and website experts indicate that it is suitable for use. Respondents gave positive responses. The developed management information system can simplify data management and make it easier to make decision data on vocational school students' field work practice.